(untitled) (The Journal of Psychology and Sociology, 2020)
Abstract. Higher education is becoming one of the key resources of upward social mobility for individuals and socio-economic development for society. The subject of this study is the analysis of the significance and value of education in Kazakhstani families, the study of what challenges are fraught with the desire of families to educate children. In particular, we will focus on the question of why the quality of education seems poor for many Kazakhstani families with sufficiently significant investments in education. We noted a high demand for higher education among the population, but also drew attention to the instrumental nature of this demand and the negative consequences arising from this circumstance. Surprisingly, one gets the impression that the widespread attitude about the need for a diploma is poorly connected with the orientation toward gaining knowledge. Moreover, disinterest in knowledge is created not only by direct consumers of services (university students), but also by employers and universities themselves. Is conditions, our answer is that in Kazakhstan a special type of universities was formed and began to dominate, focused on maximizing the profits received from students. In the absence of other types of universities, this feature is a serious problem for improving the quality of higher education in the country Key words: higher education, quality of education, diploma mills.